Mechanical Deconvolution of Elastic Moduli by Indentation of Mechanically Heterogeneous Materials - Boots, J. N. M.; Kooi, R.; Kodger, T. E.; van der Gucht, J. (Frontiers in Physics, 2021)
Most materials are mechanically heterogeneous on a certain length scale. In many applications, this heterogeneity is crucial for the material's function, and exploiting mechanical heterogeneity could lead to new materials with interesting features, which require accurate understanding of the local mechanical properties. Generally used techniques to probe local mechanics in mechanically heterogeneous materials include indentation and atomic force microscopy. However, these techniques probe stresses at a region of finite size, so that experiments on a mechanically heterogeneous material lead to blurring or convolution of the measured stress signal. In this study, finite element method simulations are performed to find the length scale over which this mechanical blurring occurs. This length is shown to be a function of the probe size and indentation depth, and independent of the elastic modulus variations in the heterogeneous material, for both 1D and 2D modulus profiles. Making use of these findings, we then propose two deconvolution methods to approximate the actual modulus profile from the apparent, blurred measurements, paving the way for an accurate determination of the local mechanical properties of heterogeneous materials.